Lyophilized amniotic membrane patch (LAMPatch) as a replacement of tamponades in the treatment of primary rhegmatogenous retinal detachment - Saravia, Mario (2020)
Background: The basis of retinal detachment repair is sealing the retinal breaks. In order to seal the retinal breaks, chorioretinal adhesion around these lesions has to be achieved. Laser retinopexy is not immediate thus necessitates the use of a temporal endotamponade to maintain both tissues in apposition. We propose the use of a patch of lyophilized human amniotic membrane (LAMPatch) in order to occlude the retinal tear effectively until the chorioretinal adhesion is settled, overcoming the risks and limitations of the current tamponades. Methods: 23-gauge vitrectomy was performed on eyes with primary retinal detachment with single retinal breaks of less than one-hour extension. A LAMPatch was deployed over the retinal breaks after retina was repositioned with perfluorocarbon. Neither gas nor silicon oil were injected. Results: Six eyes of six patients with total or partial retinal detachment were included. Retinas remained reattached in all cases until the end on follow-up (3, 5 months). Best-corrected visual acuity at 1-week postop was between 20/30 and 20/100. Neither elevations of intraocular pressure, cataracts nor signs of inflammation were registered during follow-up. No second surgeries were needed. Conclusion: This technique has proven to be safe and effective in this small case series. No intraocular pressure rise, inflammation or cataracts were registered until last follow-up visit.